2002
DOI: 10.1007/s00276-002-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Topographical analysis of lymphatic pathways from the meso- and hypopharynx based on minute cadaveric dissections: possible application to neck dissection in pharyngeal cancer surgery

Abstract: To facilitate the development of new operative procedures for pharyngeal cancer, it is important to understand the precise location of the lymph nodes and their pathways. Minute dissection of 22 neck-halves (11 adult cadavers) was undertaken to determine the location and topographical relationships of the lymphatics of the pharynx. Four groups of lymph nodes on the drainage pathways from the meso- and hypopharynx to the internal jugular nodes were classified according to their topographical relationships to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The present study also demonstrated that metastases to RPLNs were observed not only in advanced cancers but also in early cancers, further supporting the idea that RPLNs are the echelon nodes of the oropharyngeal walls [24], as Rouviere discussed [25]. It has been our policy to recommend postoperative radiotherapy to patients with three or more lymph node metastases or ECS.…”
Section: Discussionsupporting
confidence: 84%
“…The present study also demonstrated that metastases to RPLNs were observed not only in advanced cancers but also in early cancers, further supporting the idea that RPLNs are the echelon nodes of the oropharyngeal walls [24], as Rouviere discussed [25]. It has been our policy to recommend postoperative radiotherapy to patients with three or more lymph node metastases or ECS.…”
Section: Discussionsupporting
confidence: 84%
“…Six of 45 cats screened for inclusion in the study were excluded because of positive results for FIV (n = 1) or FeLV (1), heart murmur detected via physical examination (1), or patient noncompliance at the time of collection of blood samples for hematologic analysis (3). Thirty-nine cats underwent CT and ultrasonography.…”
Section: Resultsmentioning
confidence: 99%
“…The lymphatic vessels draining the nasal fossae to the retropharyngeal lymph nodes, known as Rouvière nodes, have been discussed in previous studies 1–10. But in these articles, the lymphatic flow was not directly observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous anatomical studies show only schematic diagrams1–5 that vary from this study. The lymphatic relationship between the wall of the nasal cavity and the pharynx remains unclear although the lymph pathways of the parapharynx have been demonstrated based on a series of human cadaveric dissections 6. Clinical reports show how important this area is, but the main emphasis has been on the nodes 7–10.…”
mentioning
confidence: 99%